Agile Development Methodology with cloud computing (International Journal of Engineering and Computer Science, 2014)
Combining agile development methodologies with cloud computing brings the greatest of both worlds. Agile development methodologies are very hopeful in the software industry. Agile development techniques are very practical in accepting the fact that prerequisite in a business environment changes regularly. This method used by artistic people who have understood the faults of regular software management processes & and provide a lot of opportunities to assess the direction of a project throughout the development lifecycle. Agile development processes optimize the opportunity provided by cloud computing by doing software releases iteratively, receiving user opinion more regularly & facilitate the organizations to examine quality standards at each section of the improvement. In this paper we are trying to analyze the Agile Management & development methods and its benefits conjunction with cloud computing.